TypeScript vs. JavaScript: A Comparative Analysis - -, Priyanka Gowda Ashwath Narayana Gowda (International Journal For Multidisciplinary Research, 2019)
JavaScript and Typescript are commonly used programming languages. Javascript has been the language of choice for web development for a long time because of its flexibility and vast ecosystem. Javascript employs the use of a dynamic typing system, which, although it has been effective and advantageous where rapid prototyping is needed, has not fared well when it comes to larger applications due to runtime errors and maintenance challenges. Typescript, on the other hand, is a typed superset of Javascript built and maintained by Microsoft intended to solve some of the challenges encountered when using JavaScript; the presence of types makes it so that a code written in this language is less prone to runtime errors and hence effective with larger applications. Besides, it provides improved error-checking, maintainability, and developer productivity. This paper seeks to analyze the key distinctions between JavaScript and Type-Script. The comparative analysis of the two languages is made possible by examining their impact on productivity, error prevention, and code maintainability. It reviews studies, developer experiences, and industry practices to determine optimal scenarios for each language, offering recommendations to developers and organizations for selecting the appropriate language based on project needs and team dynamics.